Growth, income distribution, and poverty: A review - Arne Bigsten; Jörgen Levin (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2001)
This paper reviews recent research dealing with the relationships between economic growth, income distribution, and poverty. This generally fails to find any systematic pattern of change in income distribution during recent decades. Neither does it find any systematic link from fast growth to increasing inequality. The level of initial income inequality is not a robust explanatory factor of growth, but some recent empirical studies have found a negative impact of asset inequality on growth. Possible channels are credit rationing, reduced possibilities for participation in the political process, and social conflicts. Among the strategic elements that have contributed to reduced poverty are: an outward-oriented strategy of export-led growth, based on labour-intensive manufacturing; agricultural and rural development, with encouragement of new technologies; investment in physical infrastructure and human capital; efficient institutions that provide the right set of incentives to farmers and entrepreneurs; and social policies to promote health, education, and social capital, as well as safety nets to protect the poor. Countries that have been successful in terms of economic growth are also very likely to have been successful in reducing poverty. Growth can be substantial if the policy and institutional environment is right.
Keywords: D31; O11; O12; I3; 330; pro-poor growth; income distribution; poverty; survey; Wirtschaftswachstum; Einkommensverteilung; Armut; Theorie